Single‐Nucleus RNA Sequencing and Spatial Transcriptomics Reveal the Immunological Microenvironment of Cervical Squamous Cell Carcinoma. Issue 29 (19th August 2022) - Ou, Zhihua; Lin, Shitong; Qiu, Jiaying; Ding, Wencheng; Ren, Peidi; Chen, Dongsheng; Wang, Jiaxuan; Tong, Yihan; Wu, Di; Chen, Ao; Deng, Yuan; Cheng, Mengnan; et al.
Abstract: The effective treatment of advanced cervical cancer remains challenging. Herein, single‐nucleus RNA sequencing (snRNA‐seq) and SpaTial enhanced resolution omics‐sequencing (Stereo‐seq) are used to investigate the immunological microenvironment of cervical squamous cell carcinoma (CSCC). The expression levels of most immune suppressive genes in the tumor and inflammation areas of CSCC are not significantly higher than those in the non‐cancer samples, except for LGALS9 and IDO1 . Stronger signals of CD56 + NK cells and immature dendritic cells are found in the hypermetabolic tumor areas, whereas more eosinophils, immature B cells, and Treg cells are found in the hypometabolic tumor areas. Moreover, a cluster of pro‐tumorigenic cancer‐associated myofibroblasts (myCAFs) are identified. The myCAFs may support the growth and metastasis of tumors by inhibiting lymphocyte infiltration and remodeling of the tumor extracellular matrix. Furthermore, these myCAFs are associated with poorer survival probability in patients with CSCC, predict resistance to immunotherapy, and might be present in a small fraction (< 30%) of patients with advanced cancer. Immunohistochemistry and multiplex immunofluorescence staining are conducted to validate the spatial distribution and potential function of myCAFs. Collectively, these findings enhance the understanding of the immunological microenvironment of CSCC and shed light on the treatment of advanced CSCC. Abstract : The high heterogeneity in viral gene expression, immune response, and metabolism in cervical squamous cell carcinoma indicates that therapies targeting multiple biological processes may yield better curative effects. The discovery of pro‐tumorigenic cancer‐associated myofibroblasts (myCAFs) in clinical samples suggests that interventions on myCAFs might complement the current treatments for invasive cervical cancer.